Bawaslu Performance in Law Enforcement Efforts Against Money Politics Violations - Daud Daniel Balubun; Faisal Santiago (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
ABSTRACT Approaching the Election, there will always be efforts by certain groups to win and increase their vote acquisition, through dirty means such as Money Politics. As an institution tasked with supervising the election process, Bawaslu must add extra-hard works to prevent election fraud so that national goals are achieved, and people's welfare is given top priority by Indonesian leaders. In working, Bawaslu is assisted by the Police and the Attorney General's Office by Article 486 paragraph (1) of Law no. 7 of 2017 concerning General Elections.